Personal trainers professional qualifications - demands of the labour market - Leśniewska, Aleksandra; Stosik, Aneta (Quality in Sport, 2016)
Fitness has been a growth industry over the past years and seems not to be saturated on the polish ground. Fitness clubs offer a wide range of services to their clients from group classes to individual trainings such as personal training. However, personal trainers in Poland have conducive and effortless way to access to their profession, they still struggle with the lack of professional standards and incoherent education; system. The main purpose of this article was to define what are the demands of the labour market in terms of required qualifications and competences for personal trainers who are taking part in recruitment process.